Clinical and inflammatory characteristics of the European U-BIOPRED adult severe asthma cohort - Shaw, Dominick E.; Sousa, Ana R.; Fowler, Stephen J.; Fleming, Louise J.; Roberts, Graham; Corfield, Julie; Pandis, Ioannis; Bansal, Aruna T.; Bel, Elisabeth H.; Auffray, Charles; Compton, Chris H.; Bisgaard, Hans; et al. (European Respiratory Society, 2015)
U-BIOPRED is a European Union consortium of 20 academic institutions, 11 pharmaceutical companies and six patient organisations with the objective of improving the understanding of asthma disease mechanisms using a systems biology approach.